Are There Ethnic Disparities in Exposure to Workplace Hazards Among New Zealand Migrants to Australia?. (November 2021) - Carey, Renee N.; El-Zaemey, Sonia; Daly, Alison; Fritschi, Lin; Glass, Deborah C.; Reid, Alison
Disparities in exposure to workplace hazards exist between Māori and non-Māori workers in New Zealand, with Māori workers generally incurring poorer conditions. This study aimed to determine if these ethnic disparities are similar after migration to Australia. A national cross-sectional telephone survey asked participants what tasks they undertook in their job to assess exposure to carcinogens as well as whether they experienced ethnic discrimination, bullying, job precariousness, or job strain. A total of 389 New Zealand Caucasians and 152 Māori/Pasifika workers were recruited. After adjustment, 79% of Māori/Pasifika compared with 67% of New Zealand Caucasian workers were assessed as being exposed to at least one carcinogen at work. Māori/Pasifika workers were also more likely to report ethnic discrimination and fair or poor current health than New Zealand Caucasians. Some ethnic disparities in exposure to workplace hazards in New Zealand are apparent after migration to Australia.